Informal Payments And Moonlighting In Tajikistan's Health Sector - Dabalen, Andrew (The World Bank, 2008)
This paper studies the relationship between gender and corruption in the health sector. It uses data collected directly from health workers, during a recent public expenditure tracking survey in Tajikistan's health sector. Using informal payments as an indicator of corruption, women seem at first significantly less corrupt than men as consistently suggested by the literature. However, once power conferred by position is controlled for, women appear in fact equally likely to take advantage of corruption opportunities as men. Female-headed facilities also are not less likely to experience informal charging than facilities managed by men. However, women are significantly less aggressive in the amount they extract from patients. The paper provides evidence that workers are more likely to engage in informal charging the farther they fall short of their perceived fair-wage, adding weight to the fair wage-corruption hypothesis. Finally, there is some evidence that health workers who feel that health care should be provided for a fee are more likely to informally charge patients. Contrary to informal charging, moonlighting behavior displays strong gender differences. Women are significantly less likely to work outside the facility on average and across types of health workers